Both species sorting and neutral processes drive assembly of bacterial communities in aquatic microcosms. Issue 2 (27th June 2013) - Lee, Jack E.; Buckley, Hannah L.; Etienne, Rampal S.; Lear, Gavin
Abstract A focus of ecology is to determine drivers of community assembly. Here, we investigate effects of immigration and species sorting (environmental selection) on structuring aquatic bacterial communities in both colonised and previously uncolonised environments. We used nonsterilised and presterilised water from three chemically distinct ponds to establish microcosms, which were opened for 12, 24, 48, 96 or 167 h and then closed again to allow airborne bacterial immigration and subsequent succession. Community similarity, richness, evenness and the parameters of a neutral model were investigated after 167 h. Immigration appeared to govern the assembly of communities in the presterilised water as there were no significant differences in evenness among microcosm communities containing water from each pond. Statistical estimation of neutral model parameters confirmed these findings, because the estimated immigration rate changed significantly with time of exposure to immigration. Species sorting also occurred because significant differences in community similarity (for presterilised and nonsterilised communities) and evenness (only for nonsterilised communities) were detected among microcosms containing different pond water; the magnitude of these differences was greater for communities in nonsterilised microcosms. Our study provides evidence for both processes being important during the colonisation of aquatic environments and presents a novel way to apply the neutral model.